Risk perception, impact, and management by farmer households in Rajasthan (India). (20th October 2022) - Kanwal, Vinita; Sirohi, Smita; Chand, Prem
ABSTRACT: The increasing frequency of droughts and floods is undermining sustainable agricultural development at the global level. The concerns are more profound in countries like India, where agriculture the primary source of livelihood is mainly rainfed. Based on the primary survey of 180 rural farm households in the highly natural disaster-prone state of India, this study elucidates how farm households perceive and respond to manage climatic shocks and associated risks. Results show that the majority of the households perceived the occurrence of adverse weather events, but a sizeable proportion of them in the drought-prone regions appear to be neglecting or downplaying the risk outcomes. The households in flood prone region were proactive in controlling and monitoring risks and resorted to multiple risk mitigation measures like diversification of crop and enterprises, changing agronomic practices, etc. The economic position of the households played the most significant role in influencing the adoption of a particular strategy. The weak empirical relationship between the communication variables and management of weather-induced risks was reflective of the lack of quality information available to the farmers through various sources.